Optimalisasi Bahan Ajar: Peran Buku Teks dan Modul Ajar dalam Pembelajaran Bahasa Indonesia - Rosmawaty Rosmawaty; Imam Mahdi; Debora Febrina Siburian (KAMPUS AKADEMIK PUBLISING, 2026)
Teaching materials are very important to support the success of learning in schools. The purpose of this study is to analyze the roles played by textbooks and teaching modules, two types of teaching materials commonly used in Indonesian language learning in schools. The study employs a descriptive qualitative approach with a literature review method. The data collected comes from various literary sources, including books, scientific journal articles, and educational documents related to the research topic. The results show that textbooks serve as the main source of learning materials, presenting concepts, examples, and exercises systematically according to the curriculum. Teaching modules, on the other hand, function as learning tools that help teachers design learning activities in a structured manner, from planning to evaluation. The combined use of textbooks and teaching modules can lead to improved learning effectiveness, as students receive clear and comprehensible materials.